Alpha-fetoprotein-elevated postpubertal testicular teratoma with retroperitoneal metastasis on 18F-FDG PET/CT: case report and literature review - Jiao, Hao; Qiu, Yongkang; Huang, Wenpeng; Zhang, Yongbai; Chen, Zhao; Wang, Aixiang; Kang, Lei (Frontiers in Medicine, 2023)
Postpubertal testicular teratoma exhibits malignant biological behavior and has metastatic potential. We report a case of a 17-year-old patient diagnosed with postpubertal testicular teratoma with massive retroperitoneal metastasis. The pathological examination revealed a mature teratoma without any other components. However, the patient had a significantly increased level of AFP, and 18F-FDG PET/CT showed the retroperitoneal metastasis had increased FDG uptake, with a SUVmax of 15.6, suggesting the coexistence of other germ cell tumor components, and the patient might have a poor prognosis. After resection of the retroperitoneal tumor, PET/CT further revealed multiple abdominal and pelvic metastases, with a SUVmax of 22.5. Therefore, the patient received a cycle of chemotherapy and follow-up PET/CT imaging showed the achievement of complete metabolic response after the treatment. In this case, PET/CT played a crucial role in detecting metastasis, compensating for the limitations of pathological sampling, thus establishing a definitive diagnosis and predicting prognosis. And it was evident that PET/CT also has the advantage of evaluating therapeutic efficacy.